Development of an agroindustry-based contextual interactive e-worksheet to improve students' understanding of statistics learning - Ngizatul Afifah; Susanto Susanto; Susi Setiawani; Dhanar Dwi Hary Jatmiko; Rafiantika Megahnia Prihandini; Arin Berliana Angrenani (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2026)
The digital transformation of Statistics learning is crucial in the technology era, as the subject's abstract nature often limits students' comprehension without contextual support. Leveraging Jember Regency's agroindustrial potential provides a meaningful context to make statistical concepts more concrete. This study aimed to develop an interactive agroindustry-based electronic worksheet (e-worksheet) integrated into the Wizer.me platform to enhance Statistics learning on measures of central tendency and measures of dispersion. Using Borg and Gall's Research and Development (R&D) model, the study involved students at SMP Negeri 4 Jember. Three experts validated both the research instruments and the developed e-worksheet. The research instruments included diagnostic and summative assessments, teacher response questionnaires, and student response questionnaires. The e-worksheet achieved validity scores of Vₐ = 3.84 (very valid) and practicality scores of Vᵤₛ = 83.42% and Vₐᵤ = 96.67% (high practicality). A paired t-test revealed a significant improvement of 25.39 points in student outcomes at the 95% confidence level, while the N-Gain score of 0.57 indicated moderate effectiveness. These results confirm that the interactive e-worksheet developed meets the criteria for validity, practicality, and effectiveness in supporting Statistics learning, while also fostering contextual learning, enhancing students' understanding, and serving as an enjoyable and engaging learning medium through an innovative digital platform.